Contrastation as a method of comprehension: a study on scientific rationalitY - Londoño Isaza, Juan David; Mejía Escobar, Jorge Antonio (Folios, revista de la Facultad de Comunicaciones y Filología, 2018)
This paper aims to explain what it means to be rational for Feyearabend, and how such quality does not correspond with the history of science nor with Mill's argument according to which science is not assisted "by the method", but through several paths that, instead of truncating its success, make the odds of success higher. Thus, we will follow Feyerabend's suggestion according to which the contrastation (of rationality and irracionality, in this case) allows for a better knowledge of the most important elements of theories.